Iconic America : our symbols and stories with David Rubenstein [videorecording (DVD)] (PBS Distribution, 2023)
Examine the history of America through some of its most iconic symbols, objects, and places, diving deep into each symbol's history and how its meaning has changed over time using them as a gateway to understanding America's past and present. From flags and statues to revered landmarks, people live alongside and interact with history every day.